Does elite European match-play affect salivary immunoglobulin-A and cortisol in soccer players? The influence of playing status and match outcome - Morgans, R.; Oliveira, R.; Rhodes, D.; Orme, P.; Ceylan, H. I.; González-Fernández, F. T.; Linán-González, A.; Moreira, A. (Frontiers in Physiology, 2024)
Introduction: The aims of this study were to: a) investigate salivary immunoglobulin A (s-IgA) and cortisol (s-Cort) responses to nine competitive fixtures in starting and non- starting soccer players; and b) compare s-IgA and s-Cort responses of starters and non-starters considering match outcome. Methods: Saliva from 19 male outfield players from an elite soccer team (mean ± SD, age 26 ± 4 years; weight 80.5 ± 8.1 kg; height 1.83 ± 0.07 m; body-fat 10.8% ± 0.7%) was collected. Saliva samples were taken on the day before each match (MD-1), 60-min before kick-off (MDpre), 30-min post-match (MDpost), and 72-h post-match (MD+3). There were five wins, one draw and three losses. Results: The mean s-IgA value was found to be significantly lower at MD+3 compared to MDpre and MDpost. s-Cort was significantly higher at MDpost compared to MD-1 and MDpre. When compared to MDpre, a statistically significant decrease in s-Cort was observed at MD+3 compared to MDpost. Starters displayed higher s-Cort values across the nine matches. There was a significant group-by-time interaction for s-Cort. There was a significant increase in s-Cort levels at MDpost compared to MD-1 and from MDpre to MDpost in starting players. At MDpost, starters had significantly higher s-Cort values. s-IgA values of starting and non- starting players following successful and unsuccessful matches did not reveal a significant difference. However, similar analysis of s-Cort in successful matches showed a significant difference between starters and non-starters. s-IgA values at MD-1, MDpre, MDpost and MD+3 in starters and non-starters following successful and unsuccessful matches revealed significant differences at MDpre and MDpost in starters, respectively. Furthermore, s-Cort values at MD-1, MDpre, MDpost and MD+3 in starters and non-starters in successful and unsuccessful matches revealed significant differences at MD+3 in starting players. Discussion: The present study suggests that in elite level soccer players, both starting status and match outcome influence s-IgA and s-Cort responses, particularly starters. Specifically, s-IgA was lower for starters before and after the match following successful outcomes. Moreover, higher s-Cort values were found before the match while lower values occurred after the match for starters in successful matches.